2020
DOI: 10.1681/asn.2020030375
|View full text |Cite
|
Sign up to set email alerts
|

Early Description of Coronavirus 2019 Disease in Kidney Transplant Recipients in New York

Abstract: Background The novel SARS-CoV-2 virus has caused a global pandemic of coronavirus disease 2019 . Although immunosuppressed individuals are thought to be at an increased risk of severe disease, little is known about their clinical presentation, disease course, or outcomes.Methods We report 15 kidney transplant recipients from the Columbia University kidney transplant program who required hospitalization for confirmed COVID-19, and describe their management, clinical course, and outcomes. ResultsPatients present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
104
1
9

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(119 citation statements)
references
References 9 publications
5
104
1
9
Order By: Relevance
“…This study also evaluated whether active replication of SARS-CoV existed in the tubular cells of postmortem patients infected with SARS-CoV by analyzing the presence of viral particles using electron transmission microscopy. The authors found that SARS-CoV was not detectable in any of the analyzed samples and suggested that renal impairment was likely related to multiorgan failure (15). This study suggested that AKI in patients with SARS-CoV could be the result of cytokine release syndrome (CRS) (68) rather than active viral replication in the kidney.…”
Section: Kidney Abnormalities Induced By Sars-cov-2: Potential Involvmentioning
confidence: 99%
See 1 more Smart Citation
“…This study also evaluated whether active replication of SARS-CoV existed in the tubular cells of postmortem patients infected with SARS-CoV by analyzing the presence of viral particles using electron transmission microscopy. The authors found that SARS-CoV was not detectable in any of the analyzed samples and suggested that renal impairment was likely related to multiorgan failure (15). This study suggested that AKI in patients with SARS-CoV could be the result of cytokine release syndrome (CRS) (68) rather than active viral replication in the kidney.…”
Section: Kidney Abnormalities Induced By Sars-cov-2: Potential Involvmentioning
confidence: 99%
“…In addition, 35% of heart specimens from SARS-CoV-infected patients revealed the coexistence of viral RNA and reduced ACE2 protein expression (52). A retrospective study during the SARS-CoV outbreak found that only 6% of SARS-CoV-infected patients exhibited AKI (15). However, AKI was a fatal complication of SARS, given that almost 92% of patients with SARS with AKI died.…”
Section: Kidney Abnormalities Induced By Sars-cov-2: Potential Involvmentioning
confidence: 99%
“…COVID-19 induces variable clinical courses in normal hosts but seems to progress more rapidly in immunocompromised hosts, with greater rates of intensive care unit admissions and death [10]. The largest series reported to date from Europe and the USA are shown in Table 1 [11][12][13][14][15][16][17]. Although there might be a bias towards selection of the most severe cases (apart from one study in which only a minority of patients had severe disease [17]), the mortality rates were between 23% and 28%, which is close to the rate of 21% reported from a cohort of 5700 hospitalized patients in New York [18], but certainly higher than the 5% usually reported for COVID-19-infected patients [11].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Although uremia and kidney transplantation are not considered a risk factor in COVID-19, SARS-CoV-2 often causes a moderate or severe infection in kidney transplant recipients. [1][2][3][4][5][6][7] Lymphopenia, increased inflammatory markers, prothrombin time, and creatine phosphokinase are prognostic factors for COVID-19. 8,9 Acute kidney injury is also associated with increased morbidity and mortality in COVID-19 patients.…”
Section: Introductionmentioning
confidence: 99%